Characterization of LaNiO3-PrNiO3 Solid Solutions as Oxygen Electrode Materials for SOEC - Yaremchenko, Aleksey (2022)
Ln2NiO4+δ (Ln = La, Pr, Nd) and its derivatives with Ruddlesden-Popper structure demonstrate high mixed ionic-electronic conductivity, moderate thermal and negligible chemical expansion, and, therefore, attract significant attention as prospective cathode materials for intermediate-temperature solid oxide fuel cells (IT-SOFC). However, Ln2NiO4+δ are thermodynamically unstable at SOFC operation temperatures and slowly decompose to a mixture of higher order Ln1+nNinO3n+1 (n = 2, 3) phases, perovskite-like LnNiO3, and LnOy. On the contrary, LnNiO3 perovskites have limited stability at elevated temperatures under oxidizing conditions. In particular, LaNiO3 decomposes on heating in air above ~1000°C. Cathodic polarization can also be expected toinduce the decomposition of the LnNiO3 perovskite phase at lower temperatures characteristic for IT-SOFC operation. At the same time, redox changes imposed by anodic polarization (in solid oxide electrolysis cell mode) under oxidizing conditions should not be of risk for the phase stability of LnNiO3. Thus, the goal of the present work was the evaluation of LaNiO3-PrNiO3 solid solutions as prospective oxygen electrode materials for solid oxide electrolysis cells. La1-xPrxNiO3-δ (x = 0, 0.2, 0.5 and 1.0) solid solutions with perovskite-like structure were prepared by combustion synthesis with calcinations in oxygen at 800-1000°C. Porous ceramic samples were sintered in oxygen at 950-1050°C. The materials were synthesized and characterized by XRD, SEM/EDS, dilatometry, TGA, coulometric titration, and electrical measurements. All prepared La1-xPrxNiO3-δ perovskites were found to be oxygen-deficient with oxygen nonstoichiometry δ slightly increasing with Pr content. The cation composition was found to have a negligible impact on the low-p(O2) stability limits: all materials decompose at log p(O2) ~ -3.5 atm at 800°C. Increasing Pr content results in a decrease in p-type electronic conductivity: from ~460 S/cm for x = 0-0.2 to 220 S/cm for x = 0.5 and 115 S/cm for x = 1.0 at 800C in air, but also reduces thermal expansion coefficient from 13.7 ppm/K for x = 0 to 11.8 ppm/K for x = 1.0 at 30-950°C in air. Comparative assessment of the electrochemical performance of La1-xPrxNiO3-δ-based electrodes in contact with (ZrO2)0.92(Y2O3)0.08 (8YSZ) and (La0.8Sr0.2)0.98Ga0.8Mg0.2O3-δ (LSGM) solid electrolytes was performed in air at 600-800°C using symmetrical cell configuration.